A disease-causing variant of COL4A5 in a Chinese family with Alport syndrome: a case series - Jing Wu; Jun Zhang; Li Liu; Bo Zhang; Tomohiko Yamamura; Kandai Nozu; Masafumi Matsuo; Jinghong Zhao (BMC Nephrology, 2021)
Abstract Background Alport syndrome (AS), which is a rare hereditary disease caused by mutations of genes including COL4A3, COL4A4 and COL4A5, has a wide spectrum of phenotypes. Most disease-causing variants of AS are located in the exons or the conservative splicing sites of these genes, while little is known about the intronic disease-causing variants. Methods A Chinese AS family was recruited in this study. All the clinical data of AS patient were collected from medical records. After pedigree analysis, the pathogenic variants were studied by the whole exome sequencing (WES). Minigene assay and in vivo RT-PCR analysis were performed to validate the functions of the variants. Results Renal biopsy showed a typical histopathology changes of AS. WES revealed compound heterozygous substitution, NM_033380 c.991–14(IVS17) A > G, in the intron 17 of the COL4A5 gene, which were confirmed by Sanger sequencing. Moreover, the variant was co-segregated with the phenotype in this family. Minigene assay in cultured cell lines showed that a splicing error was induced by this intronic variant, which further confirmed by in vivo RT-PCR analysis. Conclusion A novel intronic disease-causing variant in COL4A5 gene was identified by WES, which was the molecular pathogenic basis of AS.